Livelihood improvement of hill farmers through sustainable farming system in north eastern hill region - Laha, R; Sinha, P K; Chahal, V P; Singh, S Gojendro; Balusamy, A; J, Rajappa J; Sen, A; Das, M; Niranjan, M; Rymbai, H; Baisar, P; Singh, Naseeb; et al. (Indian Farming, 2022)
.